2017
DOI: 10.7196/samj.2017.v107i9.12124
|View full text |Cite
|
Sign up to set email alerts
|

Central-line-associated bloodstream infections in a resource-limited South African neonatal intensive care unit

Abstract: Background. The rate of central-line-associated bloodstream infection (CLABSI) in South African (SA) public sector neonatal intensive care units (NICUs) is unknown. Tygerberg Children's Hospital (TCH), Cape Town, introduced a neonatal CLABSI surveillance and prevention programme in August 2012. Objectives. To describe CLABSI events and identify risk factors for development of CLABSI in a resource-limited NICU. Methods. A retrospective case-control study was conducted using prospectively collected NICU CLABSI e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…Further, more than half ( n = 21, 60%) of the synthesised articles were from East Africa, whereas the rest were shared across northern, western, southern and central Africa (Figure 3). Only one article reported an incidence study, 14 whereas the rest were prevalence studies (retrospective or prospective). Five (14.3%) of the reviewed articles based their categorisation on specific microorganisms isolated, 15,16,17,18,19 whereas some others were based on specific HCAI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, more than half ( n = 21, 60%) of the synthesised articles were from East Africa, whereas the rest were shared across northern, western, southern and central Africa (Figure 3). Only one article reported an incidence study, 14 whereas the rest were prevalence studies (retrospective or prospective). Five (14.3%) of the reviewed articles based their categorisation on specific microorganisms isolated, 15,16,17,18,19 whereas some others were based on specific HCAI.…”
Section: Resultsmentioning
confidence: 99%
“…Five (14.3%) of the reviewed articles based their categorisation on specific microorganisms isolated, 15,16,17,18,19 whereas some others were based on specific HCAI. 14,16,17,20,21,22,23,24,25,26,35,37,38,39,44,45,46,47,48 Only eight studies (22.9%) 28,29,30,31,32,33,34,35 covered HCAI in entirety and conducted full surveillance of the different types enumerated by previous published protocols. 8,36 Eight articles (22.9%), however, did perform HCAI surveillance without the mention of the microorganisms implicated.…”
Section: Resultsmentioning
confidence: 99%
“…As highlighted by Rosenthal (2009), high CLABSI rates suggest that LMICs face significant barriers for CLABSI reduction including resources, appropriate medical supplies and adequate numbers of skilled personnel. Additional examples include inadequate and (Geldenhuys et al, 2017;Assis et al, 2018;Ider et al, 2012;The Joint Commission, 2012). outdated technologies, lines used without sterile dressings, single dose vials used multiple times covered with contaminated tape, cotton balls impregnated with contaminated antiseptic solutions and semi-rigid plastic containers used for intravenous infusate preparation.…”
Section: Limited-resource Settingsmentioning
confidence: 99%
“…Bai et al (2014) reported that with every hour's delay in noradrenaline initiation after the onset of septic shock, mortality increased by 5.3% [13]. Although CVC has long been considered necessary by clinicians for initiating vasopressors, delay in placement due to non-availability of skilled personnel may be associated with prolonged hemodynamic instability and its related complications [14]. It is possible to initiate vasopressors early if the infusion is initiated through a PVC and even forestall the use of a CVC.…”
Section: Discussionmentioning
confidence: 99%